Implementasi Raspberry Pi Embedded System Pada Kamar Mandi Pintar Untuk Monitoring Dan Otomatisasi - Valensiyah Rozika; Tibyani Tibyani; Barlian Henryranu Prasetio (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Provision of bathroom facilities are important at this time, especially with the rapid growth of tecnology in population. The bathroom is the place most often visited by everyone no exception elderly and circles disabillity. Any case fall in bathroom is high enought. Someone will awlays risk of falling at bathroom related with his condition. The impact of the fall incident in someone's at bathroom, minor injuries to death. Therefore in this reasech the reseacher made a smart bathroom system, where the system can be applied in many bathroom facilities in order to monitor and automation the bathroom. This system, gave an illustration of prototype to monitor and automation the bathroom by using rasberrypi as the microprocessor. This system gave adventages such as by the system people will know someone who might be fell in the bathroom and by the system people can save electrical energy. Testing method focused on different user. From testing result, this system has 100% value at functional testing. In testing the detection process by Raspi-camera, user 1, user 2, user 3 were detected from different angles due to differences in standing distance from each user. In testing people passing Raspi-camera, the system accuracy reached 73.3%.